2004
DOI: 10.1182/blood-2004-02-0414
|View full text |Cite
|
Sign up to set email alerts
|

Once-daily intravenous busulfan and fludarabine: clinical and pharmacokinetic results of a myeloablative, reduced-toxicity conditioning regimen for allogeneic stem cell transplantation in AML and MDS

Abstract: Postulating favorable antileukemic effect with improved safety, we used intravenous busulfan and fludarabine as conditioning therapy for allogeneic hematopoietic stem cell transplantation (HSCT) for acute myelogenous leukemia (AML) and myelodysplastic syndrome (MDS). Fludarabine 40 mg/m 2 and intravenous busulfan 130 mg/m 2 were given once daily for 4 days, with tacrolimus-methotrexate as graft-versus-host disease (GVHD) prophylaxis. We treated 74 patients with AML and 22 patients with MDS; patients had a medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
344
5
4

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 395 publications
(373 citation statements)
references
References 46 publications
20
344
5
4
Order By: Relevance
“…The initial report by the MD Anderson group of FB4 in MAC-eligible patients showed a remarkably low NRM of 14% at 3 years after SCT. 26 When this regimen was explored in older patients with more comorbidities, more similar to our FT regimen, NRM rate was also more similar, reaching 26% at 3 years. 27 Multivariate analysis showed that an HCT-CI 42 and advanced disease were the factors predicting for NRM, and when adjusting for these factors, FT conditioning was not associated with excess NRM.…”
Section: Discussionmentioning
confidence: 99%
“…The initial report by the MD Anderson group of FB4 in MAC-eligible patients showed a remarkably low NRM of 14% at 3 years after SCT. 26 When this regimen was explored in older patients with more comorbidities, more similar to our FT regimen, NRM rate was also more similar, reaching 26% at 3 years. 27 Multivariate analysis showed that an HCT-CI 42 and advanced disease were the factors predicting for NRM, and when adjusting for these factors, FT conditioning was not associated with excess NRM.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 However, favorable outcomes of non-TBI-based RIC transplantation were also reported. 8 Thus, the impact of low-dose TBI on outcomes after allo-HSCT remains controversial, and it is unknown whether the addition of low-dose TBI to RIC is beneficial for AML patients. Therefore, we conducted a retrospective analysis to elucidate the clinical impact of low-dose TBI on outcomes after allo-HSCT from a HLA-matched-related donor in the setting of fludarabine-based RIC.…”
mentioning
confidence: 99%
“…7 Based on recent publications, there is reason to believe that the sequence and timing of the respective drug may also influence outcome in the clinical setting. The concomitant use of Flu and Bu in a 4-5-day combination yields very similar outcomes, [8][9][10][11][12][13][14][15] especially in high-risk patient subpopulations. In contrast, investigators who use sequential administration of the two drugs reported similar low non-relapse mortality, but possibly a higher post-transplant relapse risk, especially in high-risk patients.…”
mentioning
confidence: 85%